1986
DOI: 10.1104/pp.80.2.470
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Response of Plasma Membranes in Tuber-Bearing Solanum Species

Abstract: ABSTRACIPermeability coefficients (Kp) of nonelectroytes were determined at several temperatures for nonacclimated and acclimated plasma membranes of the frost sensitive Solanum tuberosum and the frost resistant Solanum commersonii. In nonacclimated membranes, Kp were equal at 25°C for the two species. Kp decreased with decreased temperature in both species; however, the decrease was much greater in the frost sensitive S. tuberosum than in frost resistant S. commersonii.Kp increased with cold acclimation. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Kami-ike et al (16) examined the temperature dependence ofthe electrogenic pump of Chara corallina plasma membrane and found that the pump conductance was much more temperature dependent than the conductance ofthe passive channels. The Ea for permeation of urea and methylurea into living cells was surprisingly high, ranging from 10 to 18 kcal/mol in Solanum slices (13).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kami-ike et al (16) examined the temperature dependence ofthe electrogenic pump of Chara corallina plasma membrane and found that the pump conductance was much more temperature dependent than the conductance ofthe passive channels. The Ea for permeation of urea and methylurea into living cells was surprisingly high, ranging from 10 to 18 kcal/mol in Solanum slices (13).…”
Section: Discussionmentioning
confidence: 99%
“…H+-effiux might also occur as a 'back-leak' via the pump. Not much data is available on the effects of temperature on active and passive processes in plant membranes (13,16). Kami-ike et al (16) examined the temperature dependence ofthe electrogenic pump of Chara corallina plasma membrane and found that the pump conductance was much more temperature dependent than the conductance ofthe passive channels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations